chapter8ProblemsAndSolutions-1

# chapter8ProblemsAndSolutions-1 - Chapter 8 Exponential...

This preview shows pages 1–6. Sign up to view the full content.

Chapter 8 Exponential functions 8.1 Graph the following functions: (a) f ( x ) = x 2 e - x (b) f ( x ) = ln( x 2 + 3) (c) f ( x ) = ln( e 2 x ) Detailed Solution: See Figures 8.1. (a) x y (b) x y (c) y x Figure 8.1: Figures for solution to Problem 8.1 8.2 Express the following in terms of base e : (a) y = 3 x (b) y = 1 7 x (c) y = 15 x 2 +2 Express the following in terms of base 2: v.2005.1 - September 4, 2009 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Math 102 Problems Chapter 8 (d) y = 9 x (e) y = 8 x (f) y = - e x 2 +3 Express the following in terms of base 10: (g) y = 21 x (h) y = 1000 - 10 x (i) y = 50 x 2 - 1 Detailed Solution: (a) y = e ln(3 x ) = e x ln(3) (b y = 7 - x = e ln(7 - x ) = e - x ln(7) (c) y = e ln(15 x 2 +2 ) = e ( x 2 +2) ln(15) (d) y = 2 log 2 (9 x ) = 2 x log 2 (9) (e) y = 2 log 2 (8 x ) = 2 x log 2 (8) = 2 3 x (f) y = - 2 log 2 ( e x 2 +3 ) = - 2 ( x 2 +3) log 2 ( e ) (g) y = 10 log 10 (21 x ) = 10 x log 10 (21) (h) y = 10 log 10 (1000 - 10 x ) = 10 - 10 x log 10 (1000) = 10 - 10 x (3) = 10 - 30 x (i) y = 10 log 10 (50 x 2 - 1 ) = 10 ( x 2 - 1) log 10 (50) 8.3 Compare the values of each pair of numbers (i.e. indicate which is larger): (a) 5 0 . 75 , 5 0 . 65 (b) 0 . 4 - 0 . 2 , 0 . 4 0 . 2 (c) 1 . 001 2 , 1 . 001 3 (d) 0 . 999 1 . 5 , 0 . 999 2 . 3 v.2005.1 - September 4, 2009 2
Math 102 Problems Chapter 8 Detailed Solution: The exponential function y = a x increases on ( -∞ , ) when the base a > 1 and decreases on ( -∞ , ) when the base 0 < a < 1. (a) Base 5 is greater than 1, so y = 5 x increases as x increases. The exponents 0 . 75 > 0 . 65, so 5 0 . 75 > 5 0 . 65 . (b) Base 0 . 4 is between 0 and 1, so y = 0 . 4 x decreases as x increases. The exponents - 0 . 2 < 0 . 2, so 0 . 4 - 0 . 2 > 0 . 4 0 . 2 . (c) Base 1 . 001 is greater than 1, so y = 1 . 001 x increases as x increases. The exponents 2 < 3, so 1 . 001 2 < 1 . 001 3 . (d) Base 0 . 999 is between 0 and 1, so y = 0 . 999 x decreases as x increases. The exponents 1 . 5 < 2 . 3, so 0 . 999 1 . 5 > 0 . 999 2 . 3 . 8.4 Rewrite each of the following equations in logarithmic form: (a) 3 4 = 81 (b) 3 - 2 = 1 9 (c) 27 - 1 3 = 1 3 Detailed Solution: (a) log 3 81 = 4 (b) log 3 1 9 = - 2 (c) log 27 1 3 = - 1 3 8.5 Solve the following equations for x : (a) ln x = 2 ln a + 3 ln b (b) log a x = log a b - 2 3 log a c v.2005.1 - September 4, 2009 3

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Math 102 Problems Chapter 8 Detailed Solution: (a) ln x = ln a 2 + ln b 3 = ln a 2 b 3 x = a 2 b 3 (b) log a x = log a b - log a c 2 3 = log a b c 2 3 x = b c 2 3 8.6 Reflections and transformations What is the relationship between the graph of y = 3 x and the graph of each of the following functions? (a) y = - 3 x (b) y = 3 - x (c) y = 3 1 - x (d) y = 3 | x | (e) y = 2 · 3 x (e) y = log 3 x Detailed Solution: (a) reflected about the x -axis (b) reflected about the y -axis (c) reflected about the y -axis and shifted along the positive x -axis by 1 unit (d) y = braceleftbigg 3 x , x 0 3 - x , x < 0 The graph of y = 3 | x | is the same as y = 3 x for x 0, and is the same as y = 3 - x for x < 0. (e) stretched along the y -axis by a factor of 2 (f) y = log 3 x is the inverse function of y = 3 x , so its graph is the reflection of the graph of y = 3 x about the line y = x . 8.7 Solve the following equations for x : (a) e 3 - 2 x = 5 (b) ln(3 x - 1) = 4 (c) ln(ln( x )) = 2 (d) e ax = Ce bx , where a negationslash = b and C > 0. v.2005.1 - September 4, 2009 4
Math 102 Problems Chapter 8 Detailed Solution: (a) 3 - 2 x = ln(5), hence x = 3 - ln(5) 2 (b) 3 x - 1 = e 4 , hence x = e 4 +1 3 (c) ln( x ) = e 2 , hence x = e ( e 2 ) = e e · e (and not e 2 e !) (d) ax = ln( Ce bx ) = ln( C ) + bx , hence x = ln( C ) a - b 8.8 Find the first derivative for each of the following functions: (a) y = ln(2 x + 3) 3 (b) y = ln 3 (2 x + 3) (c) y = ln(cos 1 2 x ) (d) y = log a ( x 3 - 2 x ) (Hint : d dx (log a x ) = 1 x ln a ) (e) y = e 3 x 2 (f) y = a - 1 2 x

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern